Basic interventional radiology competency & exposure (ICE) course 2024 - Mahfudz, Anis Shafina; Hooi Lam, Tan; Mohd Khairun Jauhari, Nasuha; Sahar, Fatin Nur Jannah; Mohd Arifin, Natasha; Mohamad Ali, Norliana Dalila; Li Shyan, Ch’ng (Faculty of Medicine, 2024)
Interventional radiology (IR) is a dynamic and transformative field of medicine that utilizes imaging technologies such as x-rays, fluoroscopy, ultrasound (US), computed tomography (CT) scan and magnetic resonance imaging (MRI) to guide therapeutic procedures.